Chikungunya seroprevalence in population-based studies: a systematic review and meta-analysis - Lacita Menezes Skalinski; Aline Elena Sacramento Santos; Enny Paixão; Martha Itaparica; Florisneide Barreto; Maria da Conceição Nascimento Costa; Maria Glória Teixeira (BMC, 2023)
Abstract Background Seroprevalence studies about chikungunya infection are usually conducted after epidemics to estimate the magnitude of the attack. This study aimed to estimate the seroprevalence of CHIKV by WHO region, considering the periods of introduction of the virus in these regions and its potential to lead to epidemics. Methods We systematically reviewed Medline/Pubmed, Embase, Lilacs, Scopus and Web of Science for original articles published up to 2020. Cohort, case-control and cross-sectional studies were eligible for inclusion, based on the results of laboratory diagnosis of previous or previous and recent infection. Those conducted with symptomatic individuals were excluded. Results 596 articles were identified, 197 full-text were reviewed and 64 were included, resulting in 71 seroprevalences. Most were cross-sectional studies (92%), between 2001 and 2020 (92%), with population of all ages (55%), conducted in Kenya (10.9%), Brazil (9.4%) and French Polynesia (7.8%). The pooled estimates were 24% (95%CI 19-29; I2 = 99.7%; p < 0.00), being 21% (95%CI 13-30; I2 = 99.5%; p < 0.00) for adults, 7% (95%CI 0-23; I2 = 99.7%; p < 0.00) for children and 30% (95%CI 23-38; I2 = 99.7%; p < 0.00) for all ages. The higher seroprevalences were found in African, the Americas and South-East Asian Regions. Conclusions The great heterogeneity of seroprevalences points to the persistence of viral circulation. Even where the seroprevalence is high, the population replacement and the absence of vaccines mean that the risk of virus spread and epidemics remains. Registration PROSPERO CRD42020166227.